Chinoise Architekturen in deutschen Gärten. Ein kleines Lexikon. - Vogel, Gerd-Helge (VDG, 2014)
Seit Marco Polo mit seinem Reisebericht am Ende des 13. Jhs. die Menschen des Abendlandes für die ostasiatische Kunst und Kultur begeisterte, fungierte diese fremde Welt als Gegenbild zur europäischen Wirklichkeit. Als sich Mitte des 18. Jhs. der Landschaftsgarten in England durchsetzte, spiegelten sich in der reichen Ausschmückung der Gärten auch die Wunschwelten Ostasiens. Die chinoise Gartenmode trat ihren Siegeszug auf dem europäischen Festland gerade zu dem Zeitpunkt an, als Jean Jaques Rousseau der spätfeudalen Gesellschaft sein "Zurück zur Natur!" empfahl.

In times of post-Fordist transformation, real estate developers play a central role in urban production and extend the traditional threefold constellation "state-owner-user". This publication examines the modes of action as to developers' decision making and investment behaviour that shapes these stakeholders' action between the priorities of building quality and economic interest. By means of a survey of real estate developers and the detailed portrayal of five companies qualities in process and product are investigated which are integrated or deliberately omitted in developments. Focussing these qualities, motives relevant to action as well as internal and external factors are analysed and systemised. Based on the thesis' findings recommendations for action related to practice are given which are directed to both, communal players and real estate developers.
Project developers and urban designers. Typology of value creation strategies in the field of urban production, construction quality and economic interest.
Keywords: Kultur; Kunst; Garten; Architektur; Gartenkunst; Chinoaserie; Barock; Rokoko; Klassizismus